FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN MENGGUNAKAN SITUS TRIPADVISOR DI KAWASAN PARIWISATA KUTA SELATAN-BALI - Herayanti, Sri; Wikanatha Sagita, Putu Agus; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 6 No 2 (2018): Jurnal IPTA (December 2018), 2018)
This study aims to determine the Factors That Influence The Decision of Tourist Using The Site of www.tripadvisor.com in Bali Tourism Area South Kuta-Bali. This research using quantitative descriptive as a data analysis technique which is using factor analysis method and data processing is using SPSS versi 17.0 for Windows. Sample determination technique is using Judgemental Sampling and sampling technique is using Accidental. Data collection technique is using a questionnaire that given to 150 respondences who as a TripAdvisor app’s users who visited Tourism Destination of uluwatu Temple, Suluban Beach, Dreamland Beach, and Jimbaran Beach to get primary data. The results of this analysis illustrate that obtained 3 factors consist of 14 indicators that influence the decision of the tourist using this site of the Tourism Area in South Kuta-Bali, namely: (1) Psychological Factors, eigen value is 5,355 and 35,699% of the cumulative percentage of variance with indicator: Perceptions, Belief & Attitudes, Motivation Social Class, and Culture. (2) Personal Factors, eigen value is 1,962 and 13,083% of the cumulative percentage of variance with indicators: Lifestyle, Personality & Self Concepts, Learning, Age, Roles & Status, and Economic Environment. (3) Social Factors, eigen value is 1,339 and 8,926% of the cumulative percentage of variance with indicators: Family, Sub-Culture, and Occupation. The highest eigen value is Psychological Factors, in 5,355 of eigen value and 35,699% of the cumulative percentage of variance and this factor becomes the most dominant factor influencing the decision of tourists using www.tripadvisor.com of the Tourism Area in South Kuta-Bali.